On the Dehn functions of a class of monadic one-relation monoids - Nyberg-Brodda, Carl-Fredrik (Comptes Rendus. Mathématique)
We give an infinite family of monoids $Π _N$ (for $N=2, 3,\,… $), each with a single defining relation of the form $bUa = a$, such that the Dehn function of $Π _N$ is at least exponential. More precisely, we prove that the Dehn function $\partial _N(n)$ of $Π _N$ satisfies $\partial _N(n) \succeq N^{n/4}$. This answers negatively a question posed by Cain & Maltcev in 2013 on whether every monoid defined by a single relation of the form $bUa=a$ has quadratic Dehn function. Finally, by using the decidability of the rational subset membership problem in the metabelian Baumslag–Solitar groups $\operatorname{BS}(1,n)$ for all $n \ge 2$, proved recently by Cadilhac, Chistikov & Zetzsche, we show that each $Π _N$ has decidable word problem.